Georreferenciamento de adolescentes diagnosticados com disfunção temporomandibular no município de Curitiba - Lemes, Vanessa Carriço (2017)
Numerous factors determine the appearance of diseases, in the case of temporomandibular dysfunction (TMD) is no different. TMDs are a group of complex and multifactorial disorders that are influenced by diverse factors and present a prevalence may have variations of 05 to 60% depending on the population evaluated. The influence of social inequalities and environmental conditions on the health status of populations has been much discussed, so exploring the geographic space in which people live can be a useful tool to devise strategies for the prevention or treatment of diseases. With the advancement of new technologies, Systems Information Geographic (SIG) has become very important tools for revealing the geographical location of certain population groups with common needs. The construction of maps containing health data allows observing phenomena that are not always possible to identify with data arranged in tables. The study proposes geo-referencing adolescents with TMD patients, diagnosed through the Diagnostic Criteria for TMD Research (RDC / TMD) in the city of Curitiba-PR, through a cross-sectional epidemiological study. We selected 936 adolescents, by stratified sampling, from public and private schools in the age group between 10 and 14 of the male and female sexes. The prevalence of TMD of the total sample was 16.34%. GIS technology was useful in this exploratory study, since it allowed to observe, in the same perspective, data on the index of development of the region and temporomandibular dysfunction.